Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1136/bcr-2021-245047
|View full text |Cite
|
Sign up to set email alerts
|

Iodinated contrast media induced Kounis syndrome during coronary angiogram: a life-threatening clinical dilemma

Abstract: Kounis syndrome (KS) is a well-documented hypersensitivity vasospastic reaction induced by a variety of triggers. Clinical presentation ranges from non-specific symptoms such as dizziness and nausea to myocardial infarction. Many cases of KS were reported after the use of iodinated contrast media, mainly during radiological procedures. This report describes the case of a 46-year-old man developing coronary vasospasm and anaphylactic shock at the end of percutaneous coronary intervention. Occurrence of such pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…As known, CAG is an invasive procedure, and patients may be allergic to the contrast agent, which will cause severe hypersensitivity reactions and can be life-threatening. 11 Many scholars have explored the influencing factors related to the degree of stenosis in patients with CHD, suggesting that the history of diabetes, blood glucose level, white blood cell count, serum troponin, fibrinogen level, fibrinogen to albumin ratio, BNP level, total bilirubin, and uric acid level were independent factors on the severity of coronary artery lesions. [12][13][14][15][16][17][18] However, to date, there is still a lack of non-invasive and efficient methods to predict the need for PCI in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As known, CAG is an invasive procedure, and patients may be allergic to the contrast agent, which will cause severe hypersensitivity reactions and can be life-threatening. 11 Many scholars have explored the influencing factors related to the degree of stenosis in patients with CHD, suggesting that the history of diabetes, blood glucose level, white blood cell count, serum troponin, fibrinogen level, fibrinogen to albumin ratio, BNP level, total bilirubin, and uric acid level were independent factors on the severity of coronary artery lesions. [12][13][14][15][16][17][18] However, to date, there is still a lack of non-invasive and efficient methods to predict the need for PCI in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, oxidative stress exacerbates macrovascular damage in diabetic patients, namely by inducing the production of reactive oxygen species (ROS), which subsequently damages the endothelial system. 11 Hyperglycemia in diabetic patients also promotes protein kinase C activation and diacylglycerol production, both accelerate the development of atherosclerosis by promoting inflammatory mediators and smooth muscle cell recruitment. It has been shown that the risk of developing CHD in diabetes is highest at any age and is mainly associated with insulin resistance, type 2 diabetes, and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations